Biochar suppressed the decomposition of organic carbon in a cultivated sandy loam soil: A negative priming effect - Lu, Weiwei; Ding, Weixin; Zhang, Junhua; Li, Yi; Luo, Jiafa; Bolan, Nanthi; Xie, Zubin (Soil biology & biochemistry, 2014)
Conversion of plant residues to biochar is an attractive strategy for mitigation of atmospheric carbon dioxide (CO2) emission and enhancement of carbon (C) storage in soil. However, the effect of biochar application on the decomposition of soil organic C (SOC) as well as its mechanisms is not well understood in the sandy loam soil of North China Plain. We investigated how biochar affected the decomposition of native SOC, using stable δ13C isotope analyses by applying biochar produced from corn straw (a C4 plant, δ13C = −11.9‰) to a sandy loam soil (δ13C of SOC = −24.5‰) under a long-term C3 crop rotation. The incubation experiment included four treatments: no amendment (Control), biochar amendment (BC, 0.5% of soil mass), inorganic nitrogen (N) amendment (IN, 100 mg N kg−1) and combined biochar and N amendments (BN). Compared with Control, N amendment significantly (P < 0.05) increased total soil CO2 emission, even when combined with biochar amendment. In contrast, biochar alone amendment did not affect total soil CO2 emission significantly. However biochar, even when combined with N amendment, significantly (P < 0.05) reduced CO2 emission from native SOC by 64.9–68.8%, indicating that biochar inhibited the decomposition of native SOC and the stimulation effect of inorganic N on native SOC degradation, a negative priming effect. N addition immediately stimulated the growth of microorganisms and altered microbial community structure by increasing Gram-positive bacteria compared to Control as measured by phospholipid fatty acid. Biochar amendment did not alter microbial biomass during the 720-h incubation period except at 168 and 720 h, but significantly (P < 0.05) lowered dissolved organic C (DOC) content in soil, primarily due to sorption of DOC by the biochar. Our study suggested that biochar application could effectively reduce the decomposition of native organic C and a potential effective measure for C sequestration in the test soil of the North China Plain. •N stimulated the decomposition of native SOC.•Biochar suppressed the decomposition of native SOC and N stimulation effect.•Biochar did not alter soil microbial biomass and community structure.•Biochar effectively adsorbed DOC derived from soil.